In silico Study of Chromane Ring Compound Rubranonoside from Plumeria rubra as Anticancer Potential - Surana, Khemchand Rajendra; Mahajan, Sunil Kashinath (Trends in Sciences, 2022)
Plumeriarubra is an ornamental tree of Apocynaceae family. Plumeria rubra is a flowering plant. Flowers are very fragrant, commonly red pink or purple middle rich with yellow. Cancer is characterized through uncontrolled cell division through overcoming the numerous cell signalling pathways. Thus targeting the signalling pathway at various sites can lead to development of potential anticancer molecules. With this rational CDK2 receptors involved in cell cycle pathway was selected for the purpose of in silico analysis. Natural Products has a renowned history in cancer therapeutics. Plant derived anticancer leads have been reported since 1950. Extensive literature survey suggested that Plumeria rubra is explored for their chemical constituents along with their anticancer potential. Reported phytoconstituent i.e. rubranonoside of this plant was subjected to docking to summarise the docking scores, hydrogen bond, electrostatic bond and various decesive factors governing the protein ligand interaction. This report can be helpful further in designing in vitro and in vivo evaluations of the anticancer activity of rubranonoside. HIGHLIGHTS Molecular docking studies suggested that rubranonoside may be potential anticancer activity In silico pharmacokinetic parameters of rubranonoside were studied selected receptor Drug like properties of rubranonoside also calculated by Qikprop Rubranonoside interacting with amino acids LYS20, LEU83, ASN132, ASP143 GRAPHICAL ABSTRACT